IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 24 TAHUN 2018 TENTANG PELAYANAN PERIZINAN BERUSAHA TERINTEGRASI SECARA ELEKTRONIK DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALEMBANG - Basron Anadoyya; Maria Immaculata Yovita Adventy; Adellah; Achmad Rofiqo Ridho (Al-Mubin, 2026)
The implementation of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services at the Investment and One-Stop Integrated Service Office of Palembang City has not been effective and efficient due to the lack of professional human resources and overly complex bureaucratic procedures. This study aims to analyze the implementation of the policy using a qualitative method through documentation studies, in-depth interviews, and observations, applying Edward III's theory, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation lacks continuous socialization, training, supervision, and evaluation, while the division of tasks among organizational units serves solely to provide specialization and expertise for implementers.